Farklılıkla öğrenme yaklaşımı ile uygulanan temel hareket becerileri eğitiminin ilkokul öğrencilerinin dikkat ve motorik özelliklerine etkisi - TOPSAKAL, NURİ; BOZKURT, SİNAN (My University, 2019)
The purpose of this study was to investigate the effect of differential learning approach on attention and motor skills of elementary school students through basic movement skills education program. Total 20 students aged 9-10 years in the third grade of an elementary school in Beykoz, Istanbul participated in this study. 12 of them were boys (132,75±7,38 cm. of height, 31,50±9,57 kg. of body weight) and eight of them were girls (131,95±6,19 cm., 33,57±8,19 kg. of body weight) The Basic Movement Skills program on the Yellow Cards group of the Physical Activity Cards (PAC) prepared for the “Games and Physical Activities” classes was carried out with perspective of differential learning on the experimental group during 4 course hour for 10 weeks. “Bourdon Attention Test”, “Illinois Agility Test”, 10 and 20 m. Sprint Tests”, “Flamingo Balance Test”, “Standing Long Jump Test (STJ)”, “Sit-up Test” were carried out as a pre-test in the beginning of the study period and as and post-test at the end. The data collected were determined as descriptive statistics and according to the result of the Wilcoxon Signed-Rank Test, it was seen that there was a significant statistical difference between the pre-test and post-test points of the Attention (p<0.01), 10 m. sprint (p<0.01), 20 m. sprint (p<0.01) features of the students of the experimental group and that these features were improved for the better and there was a significant statistical difference between the pre-test and post-test points of the according to the data collected, it was evaluated that the Basic Movement Skills practices with differential learning approach can be effective on the attention and speed improvements of 3th grade elementary school students. Keywords: Differential learning, movement skills, attention, physical activities, motoric features.

Bu çalışmanın amacı, farklılıkla öğrenme yaklaşımı ile uygulanan temel hareket becerileri eğitimi programının, ilkokul öğrencilerinin dikkat ve motorik özelliklerinin gelişimi üzerindeki etkilerini araştırmaktır. Çalışma grubunu İstanbul Beykoz İlçesindeki bir İlkokulun 3. Sınıf , 9-10 yaş grubundan 12 erkek öğrenci (boy uzunluğu 132,75±7,38 cm., vücut ağırlığı 31,50±9,57 kg.) ve 8 kız öğrenci (boy uzunluğu 131,95±6,19 cm., vücut ağırlığı 33,57±8,19 kg.) olmak üzere toplam 20 öğrenci oluşturmuştur. Bu araştırmada çalışma grubuna farklılıkla öğrenme yaklaşımı ile haftada 2 gün ve 4 ders saati olmak üzere 10 hafta süresince "Oyun ve Fiziki Etkinlikler" dersleri için hazırlanmış olan Fiziksel Etkinlik Kartları ndan Sarı Kart grubundaki, Temel Hareket Becerileri alanı olan programı uygulanmıştır. Çalışmada ön test ve son test olarak “Bourdon dikkat testi”, "Çeviklik testi", "10 m. ve 20 m. koşu sürati testleri", "Flamingo denge testi", "Durarak uzun atlama testi ", “Mekik testi” yapılmıştır. Elde edilen veriler, tanımlayıcı istatistikler olarak belirlenmiş ve Wilcoxon işaretli sıralar toplamı testi sonucuna göre de deney grubu öğrencilerinin Dikkat (p<0.01), 10 m. koşu (p<0.01), 20 m. koşu (p<0.01) özelliklerinin ön ve son test puanları arasında istatistiksel açıdan anlamlı bir fark olduğu ve bu özelliklerin olumlu yönde geliştiği saptanmıştır. Elde edilen verilere göre farklılıkla öğrenme yaklaşımı ile uygulanan temel hareket beceri eğitimi uygulamalarının 3. sınıf ilkokul öğrencilerinin özellikle dikkat ve sürat özelliklerinin gelişimi üzerine etkili olabileceği değerlendirilmiştir. Anahtar kelimeler: Farklılıkla öğrenme, hareket becerisi, dikkat, fiziksel aktivite, motorik özellik.
The Effect of Basic Movement Skills Education Using the Differential Learning Approach on Attention and Motoric Features of Elementary School Students
Keywords: Differential learning; movement skills; attention; physical activities; motoric features; Farklılıkla öğrenme; hareket becerisi; dikkat; fiziksel aktivite; motorik özellik